Cu-Ni-Sn alloy fabricated by melt spinning and selective laser melting: a comparative study on the microstructure and formation kinetics - Chao Zhao; Zhi Wang; Daoxi Li; Lauri Kollo; Zongqiang Luo; Weiwen Zhang; Konda Gokuldoss Prashanth (Journal of Materials Research and Technology, 2020)
Composition modification (elemental modification) is found to be an effective method for tuning the bimodal microstructure (equiaxed and column grains) observed in the selective laser melted (SLM) metallic materials, and thereby improving their properties. However, optimization for the powder composition is a tedious task consuming energy, time and resources. One of the non-equilibrium processes, melting spinning (MS), matches the solidification conditions of the SLM process (especially the cooling rate), which offers the possibility of using the MS process as the first step in optimizing the elements/alloy design and development for the SLM process. In this work, SLM and MS processes were employed to fabricate the Cu-Ni-Sn alloy to compare the microstructural features and the resultant properties. The result reveals that the sample fabricated by MS shows a similar supersaturated structure as the SLM counterpart and both these samples exhibit analogous microstructure consisting of fine equiaxed grains, column grains, intragranular and intergranular γ-(CuxNi1-x)3Sn phase. The results confirm the possibility of using the MS process as the first step in the alloy design/development for the SLM process.